Kewajiban Dakwah: Analisis Hadis Perintah Dakwah dan Hadis Menyampaikan Kebenaran - Nasir, St. Magfirah; Juhansyah, Juhansyah (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2025)
Da´wah is one of the main obligations in Islam, with a strong foundation in the Qur’an and Hadihs. This study aims to examine the obligation of da’wah according to the hadihs of the Prophet Muhammad (peace be upon him), using a qualitative descriptive research methodology. The method employed is a literature review. Data collection techniques were carried out by examining books, journals, and other literature relevant to the topic. The research instrument used is the researcher themself, who interprets the data and readings obtained from libraries, journals, and other related sources. The data processing and analysis technique consists of three stages: 1. Data Reduction, summarizing and selecting the essential data, focusing on the most relevant information in accordance with the research topic. 2. Data Display, presenting the data in narrative form, which is then analyzed. 3. Conclusion Drawing, aimed at providing an understanding based on the researcher’s own interpretation of the data found. The purpose of these data processing and analysis techniques is to select, organize, and re-examine data sourced from books, journals and literature in order to arrive at a final conclusion. The main focus of this study includes: the command to engage in da’wah, the obligation to convey the truth and the importance of delivering da’wah to those who are unaware.